2021
DOI: 10.1111/ijcp.14508
|View full text |Cite
|
Sign up to set email alerts
|

Nasogastric tube insertion in intubated patients with the guide of wire rope: A prospective randomised controlled study

Abstract: During anaesthesia practice, nasogastric tube (NGT) insertion is one of the most frequently performed procedures in patients with wide range of diseases and conditions, from very healthy subjects undergoing elective surgeries to unconscious critically ill intubated patients.NGT insertion is one of the most frequently performed procedures in intubated patients. This procedure is a very challenging procedure in the critically ill or anaesthetised patients who cannot swallow. During the insertion, the NGT usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…In intubated or obese patients, insertion of NGT using a wire rope could be beneficial. Sharifnia et al [ 16 ] studied the use of a wire rope guide with chin lift compared to a control group with head flexion as techniques for the insertion of NGTs. They found that there was significantly higher first attempt success in the rope wire guide group for correct positioning.…”
Section: Ngt Insertionmentioning
confidence: 99%
“…In intubated or obese patients, insertion of NGT using a wire rope could be beneficial. Sharifnia et al [ 16 ] studied the use of a wire rope guide with chin lift compared to a control group with head flexion as techniques for the insertion of NGTs. They found that there was significantly higher first attempt success in the rope wire guide group for correct positioning.…”
Section: Ngt Insertionmentioning
confidence: 99%
“…Simple maneuvers such as additional flexion of the neck, 5 lateral neck pressure, 4 and reverse Sellick’s maneuver 3 were used by several authors for increasing the success rate of NGT insertion. Studies using instruments such as forceps, angiography catheters, 6 and wire rope 7 as stylets, and the use of video laryngoscopes such as C-Mac 8 resulted in success rate, but with complications.…”
Section: Introductionmentioning
confidence: 99%